EVALUASI KEBIJAKAN PERATURAN BUPATI KABUPATEN KUDUS NOMOR 37 TAHUN 2020 TENTANG PENGELOLAAN SISTEM PENGADUAN INTERAKTIF LINTAS SEKTORAL - Novan Atthoriq; R. Slamet Santoso (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2026)
The background of this research is based on the importance of digital transformation in improving the quality of public services, particularly through an application-based complaint system that includes SP4N-Lapor, Lapor Gub, and Wadul K1 and K2 integrated in the Kudus Sehat application. Problems found in this study include many complaints that have not been responded to by OPD, there are delays in complaint responses, and dissatisfied responses from Kudus Sehat application users. This study aims to evaluate the implementation of the Kudus Regency Regent Regulation Number 37 of 2020 concerning the Management of Cross-Sectoral Interactive Complaint Systems and analyze the inhibiting factors in the policy evaluation process. This study uses a qualitative approach with descriptive methods. Data collection techniques are carried out through interviews, observations, and documentation studies. The policy evaluation is analyzed using the theory of Bridgman and Davis with input, process, output, and outcome indicators, while factors inhibiting evaluation are analyzed using the theory of William N. Dunn. The results of the study indicate that in terms of process, output, and outcome indicators, the complaint system management policy has been running quite effectively, marked by the transformation of services to digital platforms, increased public participation, and a positive impact in the form of increased certainty of public service information. However, input indicators still reveal limited human resources and inconsistent budget allocations between regional government agencies (OPDs). Furthermore, policy evaluation barriers arise from the setting of performance targets for 1x24-hour complaint responses, which have not been fully achieved. This study recommends strengthening resources and adjusting performance targets to more realistic ones to improve the effectiveness of managing the interactive cross-sectoral complaint system in Kudus Regency..